CRISPR/Cas9 to generate plant immunity against pathogen. (April 2020) - Zaynab, Madiha; Sharif, Yasir; Fatima, Mahpara; Afzal, Muhammad Zohaib; Aslam, Mehtab Muhammad; Raza, Muhammad Fahad; Anwar, Muhammad; Raza, Muhammad Ammar; Sajjad, Nelam; Yang, Xuewei; Li, Shuangfei
Abstract: Different types of molecular approaches have been used for improving resistance against pathogens to secure food. Efficient and advanced genome editing tool as paralleled to earlier techniques like Zinc Finger Nuclease (ZFN), transcription activator-like effector nucleases (TALENs), and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR). The approach of CRISPR/Cas9 has updated our abilities of genetic manipulation in many crops. The assembly of purposes that can be achieved through CRISPR/Cas9 and its related products make it a powerful system that will expose novel prospects in the complex domain of plant-pathogen interactions and will help to develop crop resistance against pathogens. CRISPR/Cas9 engineering permits DNA endonuclease guided by an RNA for a range of genome engineering applications across various eukaryotic species and provides an effective platform to create resistance against bacteria, viruses, insects, and fungi. In this review, we discuss CRISPR-Cas9 engineered crop plants resistant to specific pathogens. Highlights: Resistance against diseases and higher production of crops would be helpful in maintaining food security. Different types of molecular approaches have been used for improving resistance against pathogenic genes. CRISPR/Cas9 systems will be beneficial in upcoming studies about plant–pathogen interactions.